Role of Magnetic Resonance Imaging in the Low Back Pain in Young Adults at a Tertiary Care Hospital in Northeast India - R. Harshith; Jaybrata Ray (Indian Journal of Physical Medicine & Rehabilitation)
Aims and Objectives: This study aims to evaluate degenerative changes in the lumbar spine of young adults aged 18–39 years with low back pain (LBP), using magnetic resonance imaging (MRI). It seeks to correlate MRI findings with varying levels of physical activity to gain insights into effective management strategies. Materials and Methods: A cross-sectional study was conducted from July 2023 to July 2024 at the Department of Radiology, Agartala Government Medical College and GBP Hospital. Sixty patients (aged 18–39 years) presenting with LBP were included and classified into three activity levels: routine, moderate and strenuous. MRI was performed using a 3.0 Tesla Siemens MRI machine, with standardised sequences. MRI findings were classified into disc degeneration, spinal canal narrowing, Modic changes, Schmorl’s nodes, spondylolisthesis and osteophytes. Statistical analysis was done using SPSS, with significance set at P < 0.05. Results: Out of 60 participants, 61.7% were male and 38.3% female. The majority were aged 26–39 years (76.6%). 70% had routine activities and 80% had chronic LBP. The most common MRI findings were disc desiccation (70%), disc bulge (73.3%) and type 2 Modic changes (78.3%), with disc desiccation increasing significantly with age (P = 0.037). Disc herniation and canal stenosis increased with age (P < 0.05). Spinal canal stenosis was most commonly Grade 1 (50%). Loss of lumbar lordosis was observed in 91.7% of cases, and osteophytes and facet joint sclerosis were more prevalent in older patients (P = 0.026). The L4/L5 and L5/S1 levels were most affected, with multilevel disc involvement seen in 43.3% (P = 0.012). Spinal canal stenosis, especially in severe cases, was significantly associated with disc herniation (P < 0.05). Conclusion: MRI plays a crucial role in diagnosing lumbar spine abnormalities in young adults with LBP, with degenerative changes such as disc desiccation, disc bulge and Modic changes being common with increasing age. These changes, particularly in individuals aged 26–39, emphasise the importance of early intervention and lifestyle modifications. However, some patients showed no MRI abnormalities, highlighting the multifactorial nature of LBP. MRI should be used judiciously, with conservative management prioritised in younger individuals unless red-flag symptoms or failure of conservative treatment occurs while recommending MRI for those in or over the 26–39 years age group. Limitations: The study’s cross-sectional design limits the ability to establish causality. Self-reported activity levels may introduce bias, and the lack of a control group limits the ability to differentiate between pathological and normal age-related changes. In addition, the single-centre setting may affect the generalisability of the findings. The high cost and limited accessibility of MRI in resource-constrained settings like India further complicate widespread application.